EFL University Students' Psychological Problems in Speaking - Melvina; Rani Autila; Asmija (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
EFL students do not only have linguistic problems but also psychological problems when learning English. The present study aims to describe psychological problems in speaking. This study is conducted under descriptive design. Participants in this study were 20 fifth-semester students of the English Education Department, Universitas PGRI Sumatera. The instrument used in this study is an online questionnaire. The findings indicate that although anxiety, shyness, lack of confidence, and fear of making mistakes are significant problems, respondents showed a generally neutral attitude toward these problems. However, the presence of these psychological barriers, coupled with a lack of motivation, suggests that targeted interventions are needed to improve English-speaking performance among respondents.